Reaktualisasi Konsep Mahram dalam Hadis Tentang Perjalanan Wanita Perspektif Maqasid al-Shari'ah - Holilur Rohman (State Islamic University (UIN) of Sunan Ampel, 2018)
This study discusses the actualization of the concept of mahram in the hadith about the maqasid al shari’ah. The focus of this study are: How is the editorial of the prophetic hadith about the prohibition of women’s travel without mahram? What do the scholars say about addressing women’s travel? How is the actualization of the concept of mahram in the course of women on maqasid al shari’ah? This research is a library research with a qualitative descriptive-analytical type and with a philosophical approach. The conclusion of this study, that the reason behind the prohibition of women not allowed to travel alone without mahram is a concern for women’s safety when they are alone. The statement like this, the law of the obligation of mahram for women traveling is contextual, because maqasid al shari’ah, within the context of this obligation, is to provide protection and security to women. Whereas the command to include mahram in the journey of women is basically one of the observations to protect women from unwanted possibilities. Whereas the trustee can be replaced with another guardian in the form of a protection mechanism for the community, both individually and collectively, among others through legal rules, legislation, and public policies that can lead to safer and protected trip.